The effect of high intensity warming up on jump and anaerobic power performance - Akazawa, N.; Saito, H.; Tanigawa, S.; Maeda, S. (The Journal of Physical Fitness and Sports Medicine, 2017)
[Aim] The sprint ability is associated with explosive and anaerobic power. High-intensity and short-duration muscle contraction induce postactivation potentiation (PAP) and increase physical performance. Previous evidences suggested that PAP warming up can acutely enhance muscular strength, jump ability, and sprint ability. However, the effects of PAP on explosive maximal anaerobic power performance is unclear. The aim of the present study is to examine whether PAP increases jump and maximal anaerobic power performances in elite sprinters. [Methods] Ten short-track athletes (18-22 years, 177±2m, 71±2 kg) were participated in this study. They performed PAP with 5 RM squat and control (CON) warming up conditions, using cross-over design at random order. We evaluated the height of counter movement jump (CMJ) and maximal anaerobic power output using Power max. [Results] The height of CMJ in the PAP condition was higher compared to the CON condition (P < 0.05). There was no significant difference in maximal anaerobic power output. [Conclusion] We concluded that a warming up including high-intensity squat increases jump ability, but may not induce an increase in maximal anaerobic power output.